Sünnet ve Hadisi değerlendirme ve anlamada Ehl’i Rey-ehl-i hadis yaklaşımları ve imam Şeybani - Özşenel, Mehmet (My University, 1999)
İslâm düşünce tarihinde nasları değerlendirme ve anlamada iki temel yaklaşım bulunmaktadır. Ehl-i rey ve ehl-i hadis olarak bilinen bu gruplar arasındaki tartışmaların merkezinde yeralan sünnet kavramının ilk iki asırda, tatbîkat anlamında kullanıldığı ve bununla daha ziyade Peygamber sünnetinin kasdedildiği anlaşılmaktadır. Sünnet kavramının, ilk dönemlerde ahkâm hadisleri yanında bid'atın zıddı anlamında kullanıldığını gösteren rivâyetler de bulunmaktadır. Hadis ise tedvin ve tasnif faaliyetiyle bağlantılı olarak sünnetin kayda geçmiş hali şeklinde anlaşılmıştır. Rey kavramı da itikâdî ve fıkhî konularda temelsiz ve keyfî görüş anlamında yerilmiş; bu menfî özellikleri taşımayan rey, fıkhî problemlerin çözümü için teşvik edilmiştir. Diğer taraftan fakîh sahâbîlerin hadisleri değerlendirme ve anlamada dikkate aldığı kimi ölçüler, daha sonra ehl-i rey grubunun önemli dayanaklarını teşkil etmiş; hadis rivâyetiyle tanınan bazı sahâbîler de ehl-i hadis yaklaşımına ilham kaynağı olmuştur. Hicrî birinci asrın sonlarında bu iki yaklaşımın Irak ve Hicaz'da yoğunlaştığı, birincinin Nehaî'de, ikincinin Saîd b. el-Müseyyeb'in şahsında tebellür ettiği genelde kabul edilmektedir. Hicrî ikinci asrın ortalarına doğru ise ehl-i reyin Ebû Hanîfe liderliğinde, ehl-i hadisin Mâlik'in öncülüğünde gruplaştığı bilinmektedir. İkinci asrın ortalarından itibaren karşılıklı ilmî ziyaretlerin artması sonucunda bir etkileşim meydana geldiği ve bu hususta Şeybânî ve Şâfiî'nin önemli rolü olduğu görülmektedir. Şeybânî, sünneti ikinci temel kaynak olarak gördüğünü açıkça belirtmiş; eserlerinde, merfû-muttasıl hadisler yanında, hüccet kabul ettiği için mürsel-munkatı, mu'dal, muallak türünden merfû, mevkuf ve maktû rivâyetlere de yer vermiştir. Şeybânî hadisleri hem sened, hem metin açısından değerlendirmiş; râvîlerin adâlet ve zapt özellikleri yanında tercih halinde fakîh olmalarını da dikkate almıştır. Tercihte hadisin muhtevasını arz usûlü ile değerlendirdiği, nesh, ihtiyat ve kolaylık gibi unsurları da gözönünde bulundurduğu görülmektedir.

There are two main approaches to authentication and understanding of Quranic verses and the traditions of Prophet (p.b.u.h.) in the history of Islamic thought. These are Ahlu'r-ra'y and Ahlu'l-hadith. The concept of sunnah that was in the centre of the debate between Ahlu'r-ra'y and Ahlu'l-hadith in the first two century was used in the meaning of 'practice/ application' and by this generally the Prophet's sunnah was meant. There are several narratives that shows in the early period the concept of sunnah was used in the meaning of ahadith al-ahkam. In addition of this usage it was also used as opposite of bid'ah. As a result of the activity of compilation and classification, hadith was understood as recorded sunnah. The concept of ra'y (opinion) that was considered unessential and arbitrary opinion in theological and legal matters was criticised. The ra'y that did not have those negative attributions was supported in solving legal problems. On the other hand while some criteria that were taken into consideration by the fakih companions in authentication and understanding hadith have become important bases for the Ahlu'r-ra'y; some other famous companion who were known with narration inspired the Ahlu'l-hadith. It is generally accepted that those two approaches were centred in Iraq and Hijaz at the end of first century; the former was represented by Nahai and the latter by Said b. al-Musayyab. It was known that through the mid second century Ahlu'r-ra'y was grouped under the leadership of Abu Hanifa and Ahlu'l-hadith under the leadership of Malik. From the mid second century, through the increase of mutual scientific journeys two groups mutually influenced each other; Shaibani and Shafii played an important role in this process. Shaibani, who was a prominent member of Ahlu'r-ra'y, made clear that he considered sunnah as the second basic source of Islamic Law after the Quran. He gave a considerable place to ahadith in his works. Besides narrating marfu-muttasıl ahadith, he narrated a large number of mursal-munqatı, mu'dal, and muallaq which are kind of marfu, mawquf and maqtu ahadith that are authoritative in his opinion. Shaibani authenticated ahadith not only according to their sanad but also to their text. He also took into consideration that the narrators, beside having the attribution of adalah and zabt, should be faqih in case of preference. On the other hand, it has appeared that he authenticated the content of ahadith by arz (comparison) method. Using this method he compared the content of ahadith with other sources such as Quran and Sunnah. In addition he considered some criteria such as nash, precaution and easiness in his preference of ahadith.
Keywords: HADİS